DAMPAK PSIKOLOGIS PEMBATALAN PEMBERANGKATAN HAJI TAHUN 2020 MASYARAKAT DESA JOJJOLO KECAMATAN BULUKUMPA KABUPATEN BULUKUMBA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2021)
The purpose of this study is to find out how the psychological impact of the cancellation of the Hajj departure in 2020 for the people in Jojjolo Village, Bulukumpa District, Bulukumba Regency and then presented in two substance problems, namely: 1) What was the psychological condition of the people of Jojjolo Village, Bulukumpa District, Bulukumba Regency due to the cancellation of the Hajj departure in 2017. 2020?2) How to overcome the psychological impact of the people of Jojjolo Village, Bulukumpa District, Bulukumba Regency due to the cancellation of the 2020 Hajj departure? In answering these problems, the researchers used qualitative research methods using a psychological approach and the Hajj and Umrah Management approach. The data sources of this research are Hasyim, Charuddin, Colleng, Hasniar, Suhra and Ramlah. Furthermore, the data collection method used is the method of observation, interviews and documentation. Also, data processing and analysis techniques were carried out through three stages, namely: data collection, data editing and data presentation. The results of this study showed that the psychological conditions experienced by prospective pilgrims from the community of Jojjolo Village, Bulukumpa District, Bulukumba Regency due to the cancellation of the hajj departure in 2020, from feelings of sadness, disappointment and heartache due to canceling the pilgrimage. The solution to the psychological conditions experienced by prospective pilgrims from the Jojjolo Village community is to try to accept sincerely, trustfully, and gracefully the government's decisions and the provisions of Allah swt. further improve the quality of His worship to Allah swt. pray a lot and entertain yourself by doing positive activities inside and outside the home, so that feelings of disappointment and sadness that are felt can be diverted. The research implications are as follows 1) Hopinh that there will be a special guidance from the sub-district government or local KUA which is intended for people who have canceled their pilgrimage related to psychological guidance so that people who cancel Hajj do not feel continuous disappointment. 2) Hoping that the sub-district government or from the local KUA will be able to provide an understanding and motivation to prospective pilgrims who cancel their departure that the pilgrimage is a call to worship, if it is canceled, then Allah swt. has not yet called His people to fulfill His calling. 3) Hoping that there will be assistance from all family members and all communities to strengthen and encourage each other, so that what have been experienced by prospective pilgrims does not become a burden on them so that their daily activities continue to run well.